Causes and Prevention Measures of Muscle Strain in Track and Field Athletes - Yin, Zhe (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The incidence of muscle strain is mainly due to the athletes’ exercise intensity is large, and the symptoms of muscle strain often appear. According to the combination of the data in this paper, the incidence of muscle strain is high due to the high intensity of athletics and the large physiological load, and the muscle strain is still increasing gradually. Muscle strain will not only affect the athletes’ training and competition results, the improper handling will affect the recovery of injured muscle function, and serious disability can be left behind. This paper mainly combines the incidence rate, main occurrence items and main causes of muscle strain caused by universities and athletes, as well as athletes’ physical fitness, physical condition, training plan and other issues, to prevent and intervene in muscle strain, so as to reduce the probability of muscle strain of athletes and strengthen coaches’ training arrangements and training plans. And to further ensure the health of athletes.